Analysis of the Needs for the Development of PJOK Learning Media Based on the APOWERREC Application in the Merdeka Curriculum - Ade Wahyu Asririya Nengsih (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2023)
This study aims to analyze the needs of teachers and students for PJOK learning media based on the Apowerrec application in the independent curriculum. The research data was taken from a population of PJOK teachers in elementary schools and students from SDN 149 Seluma, SDN 13 Seluma and SDN 65 Seluma in Seluma district. The data analysis technique uses a quantitative descriptive analysis technique. The data collection technique used in this study was using a needs questionnaire which was distributed directly to PJOK students and teachers. The implications of research on teachers and students to change teaching patterns in accordance with the independent curriculum. In this study the questionnaire respondents consisted of 85 students with details of 28 students from SDN 149 Seluma, 30 students from SDN 13 Seluma, 32 students from SDN 65 Seluma and 3 PJOK teachers in 3 schools in Seluma district. The data generated by using a questionnaire and analyzed then made a conclusion based on the interpretation of the results of the analysis. The data collected was in the form of the results of distributing the teacher's needs questionnaire by 87% with the category strongly agree. In the distribution of student needs questionnaires by 85% with the category of strongly agree. Based on the results of the data analysis, it was concluded that the development of instructional media is needed by both PJOK teachers and students. Based on the results of the needs analysis, the development of PJOK learning media based on the Apowerrec application in the independent curriculum will be carried out.